Processing of Sesbania Grandiflora Seed to Reduce Anti Nutritive Compounds - A Irawan Sutikno (Indonesian Center for Animal Research and Development, 1999)
Turi (Sesbania grandiflora) belongs to the family of Leguminoseae. It is potential to be developed as a feedstuff since it has a high protein content. However, it has some obstacles as it contains many anti-nutritive compounds, such as canavanine, trypsin inhibitor, saponin, tannin and alkaloids. There are many methods to remove these compounds such as by making protein concentrate and dehulling seed coat. Protein concentrate preparation gave a low yield (3.9% from original stuff). More over, the unwanted compounds only being reduced and not eliminated. Whereas dehulling process (approximately 35-40% from the whole grain) reduced more of these compounds. Dehulling seed coat is suggested to be fed to the non-ruminants. Key words : Turi (Sesbania grandiflora), anti-nutritive compounds, protein concentrate, dehulling process